CT Angiography in Patients with Peripheral Arterial Disease - Chhetri, Pramod Kumar; Thapa, Kripesh (Journal of College of Medical Sciences-Nepal, 2020)
Background: Peripheral arterial disease is one of the most important causes of morbidity. Non-invasive characterization of peripheral arterial disease is possible by using CT angiography. The aim of this research is to evaluate CT angiographic findings in patients with peripheral arterial disease, to characterize lesion, risk factors and site of lesion. Methods: This hospital based prospective study was conducted in 40 consecutive patients with lower limb peripheral arterial disease who underwent CT angiography in the Department of Radiodiagnosis College of Medical Sciences-Teaching Hospital from January 2018 to Jan 2019. Results: Atherosclerotic peripheral disease was most common in elderly male patient with history of smoking, hypertension, diabetes or dyslipidemia and usually presents in the late stages with single or multiple arterial segmental involvement including the abdominal aorta. However, non- atherosclerosis peripheral arterial disease was seen in younger patients and presents with vascular thrombosis. Conclusions: CT angiography is a reliable non-invasive imaging modality for evaluating patients with peripheral arterial disease and lesion characterization. Keywords: CTA; Peripheral arterial disease.